Good practices in secondary education institutes. A practice oriented to the use of the sociometric technique to deepen students’ knowledge - Ramos Corpas, Manuel Jesús; Castillo García, Manuel (Avances en Supervisión Educativa, 2013)
On the first part of next article it’s expounded a theoretical approximation to what “good practices” are; for it there are revised the proposals of several authors in here, there are considered different aspects for their categorization and we set a classification and a sketch model for presenting a good practice. The second part describes an example of a good practice performed in a high school, it consists on the use of the sociometric technique as the instrument for going into detail about pupils knowledge and also for setting strategies, for independent or group work intervention, with those pupils with signs of risk.